PROBLEM INSIDER DAN OUTSIDER DALAM STUDI AGAMA PERSPEKTIF RUSSEL T. McCUTCHEON - Rusdin Ahmad (Hunafa: Jurnal Studia Islamika, 2012)
Abstract: Russel T. McCutheon, a critical figure in studying and responding to the issue of religion, argued that in dealing with a modern and sophisticated life, a variety of approaches must be used to produce a theory that can be understood and accepted by all religions. In addition, no one would have felt marginalized from the structure of social life as the world inhabited by human beings sometimes makes them feel more powerful than the actual ruler. McCutheon gives an example of America and Europe in which considerable change in the structure of the understanding and culture of the community occurs because both regions have different characters and cultures. Thus, an anthropological approach to understand the character and behavior of the society and religion as a whole is necessary.Kata Kunci: insider, outsider, studi agama, Russel T. McCutcheon